Sustained expression of HPV16 E7 oncoprotein promotes p-AKT(Ser473)/p-Src(Tyr527) signaling to drive precancerous lesions to invasive cervical cancer. (4th February 2022) - Lin, Zhongmin; Zhao, Yu; Li, Qijia; Ci, Xingyuan; Ye, Xiaoxian; Chen, Guorong; Tu, Quanmei; Feng, Weixu; Jiang, Pengfei; Zhu, Shanli; Xue, Xiangyang; Saunders, Nicholas A; et al.
Abstract: Human papillomavirus (HPV) E7 oncogene plays the most important role in cervical cancer. However, whether E7 oncoprotein is continuously expressed, associated with AKT (Ser473) /p-Src (Tyr527) signaling to trigger cervical carcinogenesis remains unclear. Here, we explored first if HPV16 E7 oncoprotein could be detected in clinical biopsies and is sustainedly expressed, and then investigated how this oncoprotein interacted with AKT (Ser473) /p-Src (Tyr527) signaling in cancer progression. We used ZHPV16E7 384 affibody to detect E7 expression in HPV16-positive cervical cancer biopsies and animal tumors by immunohistochemistry (IHC). Results showed that ZHPV16E7 384 affibody had intense and specific staining for E7 oncoprotein in the detected specimen. The E7 oncoprotein was continuously expressed to correspond with the development of precancerous lesions to invasive cervical cancer. IHC staining also revealed that AKT, p-AKT (Ser473), Src and p-Src (Tyr527) proteins were expressed in both patient biopsies and animal tumors, with the highest levels of p-AKT (Ser473) /p-Src (Tyr527) present in invasive cancer. Furthermore, siRNA experiments revealed that HPV16 E7 knockdown significantly impaired expression of p-AKT (Ser473) /p-Src (Tyr527) in both HPV16 E7-positive cancer cells and transformed cells. In addition, transient expression of HPV16 E7 protein promoted significantly expression of p-AKT (Ser473)/ p-Src (Tyr527) in primary human keratinocytes. Finally, co-immunoprecipitation analysis proved that HPV 16 E7 protein interacted reciprocally with p-AKT (Ser473) /p-Src (Tyr527) . In conclusion, we demonstrate that HPV16 E7 oncoprotein is continuously expressed to promote expression of p-AKT (Ser473) /p-Src (Tyr527) leading to drive the initiation and progression of cervical cancer. Our data provide a novel insight that HPV16 E7 activates p-AKT (Ser473) /p-Src (Tyr527) to establish a mechanistic link between the oncogene and the AKT/Src signaling to trigger cervical carcinogenesis. Graphical Abstract: